2017
DOI: 10.1038/s41467-017-01611-3
|View full text |Cite
|
Sign up to set email alerts
|

Drip tectonics and the enigmatic uplift of the Central Anatolian Plateau

Abstract: Lithospheric drips have been interpreted for various regions around the globe to account for the recycling of the continental lithosphere and rapid plateau uplift. However, the validity of such hypothesis is not well documented in the context of geological, geophysical and petrological observations that are tested against geodynamical models. Here we propose that the folding of the Central Anatolian (Kırşehir) arc led to thickening of the lithosphere and onset of “dripping” of the arc root. Our geodynamic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 69 publications
9
120
1
Order By: Relevance
“…Prior work from the eastern United States, using the methods employed in our paper, similarly imaged shallow lithospheric low velocities (Savage et al, ). Alternatively, this high‐velocity overlain by low or average velocities could also be associated with some type of destabilized lithospheric root or delamination, as has been proposed for other tectonic settings (e.g., Göğüş et al, ; Shen et al, ; van Wijk et al, ; West et al, ). Such a mechanism would be expected to affect mantle flow (Shen et al, ; West et al, ), whereas for a stacked slabs scenario, the pattern may be stable, although prior metasomatism of the lithosphere may also enable subsequent destabilization (e.g., Snyder et al, ; van Wijk et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…Prior work from the eastern United States, using the methods employed in our paper, similarly imaged shallow lithospheric low velocities (Savage et al, ). Alternatively, this high‐velocity overlain by low or average velocities could also be associated with some type of destabilized lithospheric root or delamination, as has been proposed for other tectonic settings (e.g., Göğüş et al, ; Shen et al, ; van Wijk et al, ; West et al, ). Such a mechanism would be expected to affect mantle flow (Shen et al, ; West et al, ), whereas for a stacked slabs scenario, the pattern may be stable, although prior metasomatism of the lithosphere may also enable subsequent destabilization (e.g., Snyder et al, ; van Wijk et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 76%
“…Note that if crustal thickening were to occur by magmatic underplating, even larger thicknesses would be required because of the greater density of underplated material. Second, thinning of the lithospheric mantle has been proposed (Bartol & Govers, 2014;Faccenna et al, 2013;G€ o g€ us¸& Psyklywec, 2008;G€ o g€ us¸et al, 2017;Schildgen et al, 2014;S¸eng€ or et al, 2003). Isostatic relationships suggest that removal of 75-125 km of undepleted lithospheric mantle could generate the required topographic response.…”
Section: 1002/2017gc007251mentioning
confidence: 99%
“…Plateau morphology and an apparent lack of crustal and lithospheric shortening have led many authors to invoke different lithospheric and asthenospheric processes in order to produce regional uplift. Examples include: steepening, tearing, and breaking off of subducting African lithosphere; delamination of Anatolian lithosphere; lithospheric dripping; and upwelling asthenospheric thermal anomalies (Bartol & Govers, 2014;Faccenna et al, 2013;G€ o g€ us¸& Psyklywec, 2008;G€ o g€ us¸et al, 2017;Schildgen et al, 2014;S¸eng€ or et al, 2003). Each of these mechanisms invokes arrival of asthenospheric mantle at shallow depths, where it provides isostatic and/or viscous topographic support.…”
Section: Introductionmentioning
confidence: 99%
“…Clockwise rotation makes the western Transverse Range sit close to the Isabella anomaly and become the most compressional place in Southern California (Bird & Rosenstock, 1984;Nicholson et al, 1994;Raikes, 1980). The downwelling Isabella anomaly may trigger mantle upwelling in its surrounding areas (Göğüş et al, 2017) where systematical negative radial anisotropies are revealed in the asthenosphere (Figure 8). The upwelling mantle flow is possibly twisted by the right-lateral strike-slip SAF when it approaches the transition between the lithosphere and asthenosphere, resulting in a rotated pattern of flow system in the horizontal direction consistent with the observed circular pattern of azimuthal anisotropy and systematical positive radial anisotropy ( Figures 5 and 8).…”
Section: 1029/2018jb015873mentioning
confidence: 99%